2015
DOI: 10.4049/jimmunol.1401936
|View full text |Cite|
|
Sign up to set email alerts
|

PD-1 Upregulated on Regulatory T Cells during Chronic Virus Infection Enhances the Suppression of CD8+ T Cell Immune Response via the Interaction with PD-L1 Expressed on CD8+ T Cells

Abstract: Regulatory T (Treg) cells act as terminators of T cell immuniy during acute phase of viral infection; however, their role and suppressive mechanism in chronic viral infection are not completely understood. In this study, we compared the phenotype and function of Treg cells during acute or chronic infection with lymphocytic choriomeningitis virus. Chronic infection, unlike acute infection, led to a large expansion of Treg cells and their upregulation of programmed death-1 (PD-1). Treg cells from chronically inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 58 publications
7
134
1
Order By: Relevance
“…The role of exhaustion markers (particularly PD-1) on Treg function remains controversial, as it was demonstrated in malignant gliomas that PD-1 hi Treg was dysfunctional and produced IFNγ (26). Others have described that PD-1 expression is correlated with more suppressive Treg phenotypes in chronic viral infection (27). Our data, however, have clearly demonstrated a correlation between Treg suppression and exhaustion-marker expression.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The role of exhaustion markers (particularly PD-1) on Treg function remains controversial, as it was demonstrated in malignant gliomas that PD-1 hi Treg was dysfunctional and produced IFNγ (26). Others have described that PD-1 expression is correlated with more suppressive Treg phenotypes in chronic viral infection (27). Our data, however, have clearly demonstrated a correlation between Treg suppression and exhaustion-marker expression.…”
Section: Discussioncontrasting
confidence: 56%
“…First, we focused on Tregs, given their well-established correlation with poor prognosis in various cancers, including HCC (23)(24)(25). Recent studies have also demonstrated the expression of exhaustion markers on Tregs, in particular PD-1, and their effect on Treg function (26,27). We then examined whether the Tregs expressed different immune exhaustion markers between the TIL, NIL, and PBMC groups.…”
Section: Lag-3mentioning
confidence: 99%
“…The function of PD-1 on the surface of Tregs is not entirely known (33,34). PD-1 hi Tregs in the TME in glioma patients have been found to be exhausted, yet capable of generating proinflammatory cytokines, such as IFN-γ (35).…”
Section: Discussionmentioning
confidence: 99%
“…During chronic infection, Tregs can suppress CD8 ϩ T cell activity in a contact-dependent manner (59). In this study, we investigated whether Foxp3 ϩ Tregs were in contact with and potentially inhibiting follicular SIV-specific CD8 ϩ T cell function.…”
Section: Foxp3 ؉ Cells Likely Inhibit Follicular and Extrafollicular mentioning
confidence: 99%